Transformational Leadership in Middle Management: Its Impact on Entrepreneurial Orientation and Social Network in Performance at a Banking Industry Company - Vannia, Adji Mayumi; Sudhartio, Lily (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The sector of banking plays a strategic role in driving the economy of the country. The growth of this sector can help the economy but also increases the intense competition in Indonesia. To improve performance, banking companies need to maintain good relationships with external parties. The role of branch offices, which interact directly with customers and stakeholders, is considered important to understand market conditions and customer needs. Branch offices have the responsibility to interact directly with customers to understand their needs, where the branch head holds a crucial role in executing this responsibility. This study explores the influence of transformational leadership possessed by the branch head on entrepreneurial orientation, social network, and performance at a branch office of a banking industry company. This study uses a quantitative method, where data collection was done through a survey. The unit of analysis is a branch office with a total of 49 branch heads. The results of the study show that transformational leadership has a significant influence on entrepreneurial orientation and social network. Most respondents, alumni of Management Trainee programs placed in various branch offices, thus having extensive knowledge about the company and high adaptability skills. The branch head, as middle management, plays a crucial role in creating a work environment that supports innovation and collaboration. It was found that the ability of branch offices to interact well internally and externally can increase the financial and customer performance of the branch office.